Persepsi Orang Tua terhadap Teman Sebaya Siswa Sekolah Dasar - Wina Mustikaati; Ela Hayati; Afrilia Afrilia; Istiba Hikmatul Anwar; Siti Hanisa Mulyani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to describe how parents perceive the influence of peers on the development and behavior of students at the primary school level. The background of this study is based on the important role of the social environment, especially peers, in shaping children's character, which cannot be fully replaced by the family environment. The method used in this study is a descriptive qualitative approach, with data collection conducted through questionnaires distributed to 30 parents of elementary school students. The results showed that the majority of respondents (60%) considered peers to be very important and acknowledged a great influence on children's behavior (66.7%). However, the level of concern over potential negative impacts was also quite high, with 70% of respondents expressing great concern. These findings identify parents' awareness of the importance of social interactions for children's development, while also pointing to the need for active parental assistance. The implications of this study emphasize the importance of collaboration between families and schools in creating a healthy social environment, to support children's optimal character development.